Turning down the gas: what is the potential for microbial detection of methane leakage from soils? - Bott, Tom (2022)
Methane is a potent greenhouse gas. Emissions from soils, wetlands and subsurface sources are therefore a concern when trying to understand greenhouse gas emission and fluxes in the environment. Soil microbial communities can act as a sink for methane, mitigating its release. The purpose of the thesis was to test if terrestrial natural gas flux could be detected using changes in the soil microbiology, focussing upon changes in the relative abundance of methanotrophs. Two methane mono-oxygenase genes were focussed upon, pmoA, mmoX and Methylocella spp. mmoX. To detect these genes PCR and qPCR assays for use with soil samples were developed using existing primer sets. Next-generation amplicon sequencing, of the 16S rRNA gene, was also used to better explore community changes.